Information Entropy and Scale Development. (23rd October 2020) - Friesner, Daniel; Bozman, Carl; McPherson, Matthew; Valente, Faith; Zhang, Anqing
Abstract: A wide variety of techniques are used to assess the development of survey-based scales. The majority of these techniques focus on the quality of information characterized by the scale. Aside from very rudimentary measures such as response rates and sample sizes, very few empirical techniques are available to measure the quantity of information contained in a scale. This article conducts an exploratory empirical analysis to assess whether information entropy can be useful for measuring the quantity of information in a scale's development. If the quantity of information in the scale significantly increases (decreases) with the addition of the survey item, researchers may consider retaining (discarding) that item in the scale. The study was conducted within the context of a natural experiment that occurred at a major amateur sporting event in 2018. Customer satisfaction was assessed using a survey whose core questions have been assessed repeatedly over time. The most recent survey contained a previously validated empathy scale, with two items contained in the base measure. Six additional items were added to this base empathy measure. The quantity of information provided (as measured by information entropy) is calculated for each set of scale items. Statistical analysis indicates that, when adding the behavioral, cognitive, and affective scales to the two-item base scale, the quantity of information available increased. However, most of the increase in information quantity was attributable to three survey items, one item from each of the behavioral, cognitive, and affective domains. These findings suggest that information entropy may indeed be a useful quality control tool for survey scale development.